Narratives About Partnership in Chilean Heterosexual Men: Between Machismo and Equality; [Narrativas Sobre Las Relaciones de Pareja en Hombres Chilenos Heterosexuales: Entre el Machismo y la Igualdad] - Valenzuela-Somogyi, M (Universidad Austral de Chile, 2023)
Drawing from the analytical perspective of the processes of individuation in contemporary Chilean society, in this study we present the results of an exploratory qualitative study of the narratives about partnership elaborated by heterosexual men with completed higher education and with an adult age range through semi-structured interviews. The results show how individual work to support themselves in response to the demand for horizontality in relationships between sexes, elaborated from an interpretive framework based on a traditional hierarchical model embodied by previous generations, implies a constant reference to themselves from the meanings associated with machismo and the tensions arising from the sustenance of male authority within the provider role. They also demonstrate how the reading that guides the production of narratives about partnerships is articulated from the expansion of democratic principles associated with the ideal of social equality, thus distinguishing from the studies that have approached the subject. © 2023, Universidad Austral de Chile. All rights reserved.